The Acute Hepatic NF-κB-Mediated Proinflammatory Response to Endotoxemia Is Attenuated in Intrauterine Growth-Restricted Newborn Mice - Zarate, Miguel A.; De Dios, Robyn K.; Balasubramaniyan, Durganili; Zheng, Lijun; Sherlock, Laura G.; Rozance, Paul J.; Wright, Clyde J. (Frontiers in Immunology, 2021)
Intra-uterine growth restriction (IUGR) is a relevant predictor for higher rates of neonatal sepsis worldwide, and is associated with an impaired neonatal immunity and lower immune cell counts. During the perinatal period, the liver is a key immunologic organ responsible for the NF-κB-mediated innate immune response to inflammatory stimuli, but whether this role is affected by IUGR is unknown. Herein we hypothesized that the newborn liver adapts to calorie-restriction IUGR by inducing changes in the NF-κB signaling transcriptome leading to an attenuated acute pro-inflammatory response to intraperitoneal lipopolysaccharide (LPS). We first assessed the hepatic gene expression of key NF-κB factors in the IUGR and normally grown (NG) newborn mice. RT-qPCR analysis revealed an upregulation of both IκB proteins genes (Nfkbia and Nfkbib), and the NF-κB subunit Nfkb1 in IUGR vs NG. We next measured the LPS-induced hepatic expression of acute pro-inflammatory genes (Ccl3, Cxcl1, Il1b, Il6, and Tnf), and observed that the IUGR liver produced an attenuated acute pro-inflammatory cytokine gene response (Il1b and Tnf) to LPS in IUGR vs. unexposed (CTR). Consistent with these results, LPS-exposed hepatic TNF-α protein concentrations were lower in IUGR vs. LPS-exposed NG, and did not differ from IUGR CTR. Sex differences at the transcriptome level were observed in the IUGR male vs. female. Our results demonstrate that IUGR induces key modifications in the NF-κB transcriptomic machinery in the newborn that compromised the acute pro-inflammatory cytokine gene and protein response to LPS. Our results bring novel insights in understanding how the IUGR newborn is immunocompromised due to fundamental changes in NF-κB key factors.